Getting the best of carbon bang for mangrove restoration buck - Jingfan Zhang; Zhe Lu; Jinge Zhou; Guoming Qin; Yicheng Bai; Christian J. Sanders; Peter I. Macreadie; Jiacan Yuan; Xingyun Huang; Faming Wang (Nature Communications)
Abstract Mangrove loss has reduced its carbon (C) sink function and ecosystem services. To effectively allocate climate finance for mangrove restoration, a thorough assessment of restoration potential is necessary. Here we show a net loss of ecosystem service value (ESV) of 29.2 billion USD ($) due to land changes in mangroves from 1996 to 2019. The estimated mangrove ESV in 2019 amounts to $894 billion yr−1, mainly provided by regulating and provisioning services (57.4% and 19.7%). Over the next two decades, we project that the restoration of mangroves would necessitate an investment of $40.0–52.1 billion, yielding net gains in ESV of $231–725 billion. The global benefit-cost ratio (BCR) of mangrove restoration ranges from 6.35 to 15.0, demonstrating that such projects are highly cost-effective. Furthermore, an estimated of 19.4 Tg C can be sequestrated in mangrove soils based on a 20-year mangrove restoration program, which can generate $68.6–$236 million via blue C trading. Our findings highlight the significant opportunities for blue C restoration projects to mitigate climate change and support livelihoods.